The Hamadan Hoard of 1977 - Lorber, Catharine C. (KOINON: The International Journal of Classical Numismatic Studies, 2024)
The hoard presented here was reportedly acquired in Hamadan (ancient Ecbatana). It was carried by an Iranian dealer to Washington, DC, where it was documented by Arthur Houghton in August 1977. Houghton purchased some coins from the hoard, photographed a substantial portion in large groups, and recorded die links and die axes for all the coins. In his extensive notes, Houghton used the designation “A” for coins in the group photos and the designation “B” for the remainder. These distinctions are included in the catalogue of the hoard. Some coins in the group photos were later photographed separately, either by Houghton himself or by Silvia Hurter for the initial publication of Houghton’s collection. The Hamadan, 1977 hoard provides a large sample of the silver coinage that circulated in Media during the first half of the 2nd century BC. It allowed for the first recognition of features that point to the operation of a number of different mints in the region and contributed importantly to the classification proposed in Seleucid Coins. The present paper differs slightly from Seleucid Coins in its proposals for specific locations for some these mints.